Determinants of outpatient healthcare-seeking behaviors among the rural poor affected by chronic conditions in India: a population-based cross-sectional study in seven states - Grossmann, David; Srivastava, Swati; Winkler, Volker; Brenner, Stephan; Gupta, Keerti Jain; Paliwal, Amit; Singh, Kavita; De Allegri, Manuela (Global health action, 2025)
A rising burden of chronic non-communicable diseases (CNCDs) increases demand for outpatient healthcare. Yet, evidence on preferences and barriers to healthcare services for India's most disadvantaged population, the target of India's largest public health insurance scheme (PM-JAY), is lacking. We explore determinants of outpatient healthcare-seeking behavior among PM-JAY eligible individuals with CNCDs in rural areas of seven states. Using cross-sectional data from a household survey (conducted between November 2019 and March 2020), we employed multilevel multinomial logistic regression to identify factors associated with seeking care from informal (home treatment, pharmacies, traditional healers), formal public, or formal private providers, compared with no care. Anderson's behavioral model informed the selection of independent variables. Of 51,820 individuals, 5,061 (9.8%) reported a chronic condition. Despite their disease, 1,168 (23.1%) reported not using regular outpatient care. Another 2,421 individuals (48.0%) used formal private, 922 (18.3%) used formal public, and 535 (10.6%) used informal care. Predictors of formal private care were higher socioeconomic status (RRR = 2.441, 95% CI [1.61, 3.70]) and health insurance coverage (RRR = 1.478, 95% CI [1.12, 1.95]). Residents of Tamil Nadu, Kerala, and Gujarat were more likely to use formal public care (RRR = 23.915, 95% CI [9.01, 63.44]). Suffering from Major CNCDs or experiencing limitations in daily activities increased the probability of using healthcare across all options. Future research should explore the reasons for non-utilization of chronic care and the preference for private providers. Policies to enhance public healthcare utilization and expand insurance for outpatient care could improve access and reduce health inequities. Main findings: Among India's rural populations, outpatient health service use for chronic non-communicable diseases is largely concentrated in the private sector and primarily determined by a patient's socioeconomic status.Added knowledge: We shed light on healthcare-seeking behavior for socioeconomically disadvantaged individuals eligible for India's largest publicly funded health insurance system and highlight substantial interstate disparities in public healthcare utilization.Global health impact for policy and action: To meet the 2030 Sustainable Development Goals, India's public healthcare system must be strengthened to provide equitable access to effective chronic disease treatment, improve health outcomes, and tackle the growing global burden of chronic non-communicable diseases. Main findings: Among India's rural populations, outpatient health service use for chronic non-communicable diseases is largely concentrated in the private sector and primarily determined by a patient's socioeconomic status. Added knowledge: We shed light on healthcare-seeking behavior for socioeconomically disadvantaged individuals eligible for India's largest publicly funded health insurance system and highlight substantial interstate disparities in public healthcare utilization. Global health impact for policy and action: To meet the 2030 Sustainable Development Goals, India's public healthcare system must be strengthened to provide equitable access to effective chronic disease treatment, improve health outcomes, and tackle the growing global burden of chronic non-communicable diseases.
Gesehen am 22.10.2025